Open education find OER (by discipline) [electronic resource] - Virginia Polytechnic Institute and State University. University Libraries; MERCED-I (Mindanao Educational Resources for Curricular Enhancement and Development-Initiatives) on OER (Open Educational Resources). (Blacksburg, VA Virginia Polytechnic Institute and State University, 2017)
Quoted from the homepage: On these pages you will find textbook and non-textbook open educational resources. Discipline-specific pages are not intended to be exhaustive, but to showcase content that may be of interest to faculty considering adopting open educational resources for use in their classes. For more information about Creative Commons including license descriptions, please see the Creative Commons tab.
University Library (UL)
mixed.
online.
Keywords: Electronic information resources; Internet research; Internet in higher education; Open learning; Education, Higher; Electronic books; College teaching -- Aids and devices -- Open educational resources. .; Education, Higher -- Aids and devices -- Open educational resources. .